Toxicity of the effluent from an anaerobic bioreactor treating cereal residues on Lactuca sativa - Young, Brian Jonathan (2012)
Effluents generated during the process of anaerobic digestion should be treated before their disposal into the environment. The aim of this study was evaluating the effectiveness of the effluent treatment system from an anaerobic bioreactor, assessing the toxicity reduction with the Lactuca sativa seed germination and root elongation inhibition test. Three sampling points were selected along the effluent treatment system: inflow into the first treatment pond, outflow from the third pond and recirculated flow to the bioreactor. Effluent dilutions tested for each sampling point were 25% and 50% (v/v), undiluted sample and controls. The pH, conductivity, temperature, dissolved oxygen, BOD5 and COD were measured. The decrease in the organic and inorganic loads was correlated with a reduction in the phytotoxicity. The use of the seed toxicity test allows evaluating the quality and effectiveness of the studied effluent treatment system